2021
DOI: 10.33824/pjpr.2021.36.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences on COVID-19 Related Anxiety Among Students

Abstract: The COVID-19 pandemic creates complex problems and in almost all aspects of life, everyone has been anxious, worried, and panicked about survival. Starting with children, young and old, men and women feel anxious about the threat of COVID-19. This study aimed to determine the differences in anxiety levels between male and female students during the COVID-19 period based on the Hamilton Anxiety Rating Scale (Hamilton, 1969). This study used a survey method with a descriptive design. Sampling using accidental sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The findings reinforce that overthinking is one of the causes of anxiety. A changed environment and poor adaptability may also cause anxiety which, if not controlled, may lead to further psychological disorders (Thahir et al, 2021). Based on the participants" views, the present study also suggests that though speaking English is the main cause of anxiety, yet it is exacerbated due to a lack of exposure at school and college levels and the past experiences of the participants.…”
Section: Discussionmentioning
confidence: 60%
“…The findings reinforce that overthinking is one of the causes of anxiety. A changed environment and poor adaptability may also cause anxiety which, if not controlled, may lead to further psychological disorders (Thahir et al, 2021). Based on the participants" views, the present study also suggests that though speaking English is the main cause of anxiety, yet it is exacerbated due to a lack of exposure at school and college levels and the past experiences of the participants.…”
Section: Discussionmentioning
confidence: 60%
“…Based on research conducted by Thahir & Bulantika (2021), it is said that mindfulness exercises can reduce the fear of missing out on social media. With the provision of mindfulness therapy, individuals will be trained to find body reactions, emotions, reduce negative thoughts and promote positive thinking.…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness therapy itself has a good effectiveness in lowering the tendency to fear of missing out or FoMO in generation Z Instagram users. This statement is based on research that has been conducted by Thahir & Bulantika (2021), namely found results that after group counseling interventions with mindfulness therapy exercises showed that there was a decrease in the score at the level of fear of missing out. In general, group counseling with mindfulness therapy exercises is capable and effective in reducing FoMO and can be used for the first step in preventing or reducing mild fear of missing out in students who use social media (Thahir & Bulantika, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals feel comfortable and do not worry whether their behaviour will be judged negatively (Bulantika & Sari, 2019). Yet, people tend to adopt such norms quickly since they assume others will think and do the same the way they do (Thahir et al, 2021). Therefore, individuals with high cognitive empathy are better able to understand, read, and imagine people's points of view, perspectives, or emotions (cognitive empathy), thus, it will be likely more related to ignoring people who talk to them, which refers to phubbing behaviour.…”
Section: Introductionmentioning
confidence: 99%